Implementation Of Attention Mechanism And Explainable Ai For Skin Lesion Classification Using CNN - Aditya Dwiputro Wicaksono; Lisda Lisda; Ilham Nur Fajri (Universitas Budi Darma, 2026)
Skin lesions are critical dermatological indicators that require early detection to prevent severe outcomes such as melanoma. Traditional Convolutional Neural Network (CNN) architectures employed for categorizing these lesions frequently encounter significant hurdles, notably disproportionate class distributions and a lack of transparency, functioning essentially as opaque